20/20 visions : collaborative planning and placemaking - Charles, Campion (London : RIBA Publishing, 2018)
20/20 Visions is an inspiring and visually stimulating introduction to the practice of participatory planning, featuring a set of 20 international case studies that illustrate the effectiveness of engaging communities and stakeholders in the participativedesign process
1. The History of Collaborative Planning 2. Collaborative Planning - Why is it Needed? 3. Collaborative Planning - What is it? 4. 20/20 Case Studies 5. Lessons from the Case Studies 6. The Way Forward for Collaborative Planning
Includes bibliographical references (page 135) and index.
ARC
Trim Education
Keywords: City planning; Kollaboration; Architecture